Trade and Factor Mobility with Increasing Returns to Scale - J.V. Henderson (Queen's University, Department of Economics, 1972)
This paper examines equilibrium and changes in equilibrium in international trade under conditions of increasing returns to scale in production. The first section of the paper solves for stable equilibrium positions between two trading partners; the reader should find this section a refinement and development of Matthews(1950) work. The second section discusses inter-country and intra-country factor mobility and examines various equilibrium and welfare positions. The role of increasing returns to scale in urban and regional production as opposed to their role in international trade is discussed. Also, the concept of equilibrium unemployment is examined. Finally the Stolper-Samuelson and Ryczynski theorems are re-evaluated for increasing returns to scale in a brief summary emphasizing the economic interpretation of the results in Jones(1968).
Keywords: 330